Modeling the Greenland Ice Sheet's Committed Contribution to Sea Level During the 21st Century. Issue 2 (15th February 2023) - Nias, Isabel J.; Nowicki, Sophie; Felikson, Denis; Loomis, Bryant
Abstract: Mass loss from the Greenland Ice Sheet can be partitioned between surface mass balance and discharge due to ice dynamics through its marine‐terminating outlet glaciers. A perturbation to a glacier terminus (e.g., a calving event) results in both an instantaneous response in velocity and mass loss and a diffusive response due to the evolution of ice thickness over time. This diffusive response means the total impact of a retreat event can take decades to be fully realized. Here we model the committed response of the Greenland Ice Sheet by applying perturbations to the marine‐terminating glacier termini that represent recent observed changes, and simulating the response over the 21st century, while holding the climate forcing constant. The sensitivity of the ice sheet response to model parameter uncertainty is explored within an ensemble framework, and Gravity Recovery and Climate Experiment data is used to constrain the results using a Bayesian calibration approach. We find that the Greenland Ice Sheet's committed contribution to 21st century sea level rise is at least 33.5 [17.5 52.4] mm (25th and 75th percentiles in brackets), with at least 6 mm being attributable directly to terminus retreat that occurred between 2007 and 2015. The spread in our projections is driven by uncertainty in the basal friction coefficient. Our results complement the ISMIP6 Greenland projections, which report the ice sheet response to future forcing, excluding the background response. In this way, we can obtain estimates of Greenland's total contribution to sea level rise in 2100. Plain Language Summary: At the edges of the Greenland Ice Sheet are fast‐flowing glaciers that flow into the ocean. When the ice front of these glaciers retreat, through iceberg calving and submarine melt, the ice sheet responds both on quick timescales, due to the instantaneous speed up of the ice near the edge, and on longer timescales as the ice dynamics slowly readjust to the initial changes. The slow readjustment of the ice sheet thickness and velocity spreads upstream over time. Therefore, even if climate change (e.g., atmospheric and oceanic warming) was to cease, the ice sheet will continue to respond to changes we have already observed, and will contribute to sea level rise. This contribution is known as "committed sea level rise, " which we quantify in this study using a numerical ice sheet model of the Greenland Ice Sheet. We find that glacier retreat between 2007 and 2015 has a lasting impact on ice sheet dynamics by the end of the century and that this should be accounted for in projections of sea level rise. Key Points: Glacier terminus position change has a lasting impact on velocity and mass loss of Greenland Greenland's committed sea level response by 2100 is comparable to that due to RCP2.6 forcings Satellite observations can constrain uncertainty in probabilistic ice sheet model projections